2009
DOI: 10.1155/2009/351369
|View full text |Cite
|
Sign up to set email alerts
|

Residual Stress Fields due to Varying Tack Welds Orientation in Circumferentially Welded Thin-Walled Cylinders

Abstract: The local, nonuniform heating and subsequent cooling during the welding processes causes complex thermal stress/strain fields to develop that finally leads to residual stresses, distortions, and their adverse consequences. Residual stresses are of prime concern to the industries producing weld-integrated structures around the globe because of their obvious potential to cause dimensional instability in welded structures, contribute to premature fracture/failure, along with the significant reduction in fatigue s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…The von Mises yield criterion, provided by Eq. ( 7), is the most extensively used plasticity model by many researchers where 1 , 2 and 3 are the principal stresses [43][44][45][46][47].…”
Section: Thermo-mechanical Methods For Waam Process: Parameters Heat Source and Plasticity Modelmentioning
confidence: 99%
“…The von Mises yield criterion, provided by Eq. ( 7), is the most extensively used plasticity model by many researchers where 1 , 2 and 3 are the principal stresses [43][44][45][46][47].…”
Section: Thermo-mechanical Methods For Waam Process: Parameters Heat Source and Plasticity Modelmentioning
confidence: 99%
“…Welding stresses originate from the restrained welding distortion. Many research papers 2451 describe the models used to find the welding distortion and welding residual stresses. To get the exact model, the field describes the specimen of metal needed to be able to change its volume and shape; along with this, properties of the materials are required like specific heat, plasticity, Poisson’s ratio and density.…”
Section: Welding Heat Flowmentioning
confidence: 99%
“…It was concluded that axial residual stresses also depend on the different orientation of tack welds at an axial part 180 o from the beginning of weld location for the inner and outer planes. 29,30 Validation on the distribution of the temperature and residual stresses which were induced due to TIG welding of SS 304 was done by Deng. 31 Investigation on the welding residual stress in HAZ of cruciform hollow sectional welded tube joint was done by Brar and Singh.…”
Section: Welding Heat Flowmentioning
confidence: 99%
“…4 With the change in the orientation of the welding, there is great change in the welding distortion. 5 Simulation of the submerged arc welding process was done using the commercial software ANSYS. The temperature distribution and the angular displacement of the mild steel welded plate were compared with the experimental data of Arora et al 6 and found the good agreement with conclusion that the double-ellipsoidal heat source is more accurate than the Gaussian heat source distribution.…”
Section: Introductionmentioning
confidence: 99%